Mengapa Rezim Internasional Gagal? Analisis Legalisasi “Lima Poin Konsensus ASEAN” tentang Myanmar Pasca Kudeta Militer 2021 - Indra Kusumawardhana (Indonesian Perspective, 2022)
Assessing the effectiveness of international regimes has become a central topic for scholars and policymakers. Realist argues that national interests determine whether or not states comply with international regimes. This article offers an alternative account by analyzing the anatomy of the agreement. Using the case study of the “ASEAN Five-Point Consensus” on Myanmar, this article employs the concept of legalization derived from institutionalist theory which is used to assess the degree of institutionalization of the international agreements characterized by three dimensions; obligation, precision, and delegation. The central thesis of this article is that the “ASEAN Five-Point Consensus” on Myanmar is a sort of soft law due to its strong weakness in three dimensions. It implies that the agreement will not be properly implemented by ASEAN member countries, especially by Myanmar’s military junta. This article concludes that the effectiveness of the “ASEAN Five-Point Consensus” on Myanmar depends not only on the states’ national interests but also on the degree of institutionalization of this agreement. The soft law character of this agreement is strongly influenced by the culture of ASEAN’s decision-making mechanism which puts a strong emphasis on the consensus in crafting non-obligatory agreements.